2022
DOI: 10.3389/fcimb.2022.882302
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Bacterial Microbiota Composition and SARS-CoV-2 IgG Antibody Maintenance in Asymptomatic/Paucisymptomatic Subjects

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes the coronavirus disease 2019 (COVID-19), ranging from asymptomatic conditions to severe/fatal lung injury and multi-organ failure. Growing evidence shows that the nasopharyngeal microbiota composition may predict the severity of respiratory infections and may play a role in the protection from viral entry and the regulation of the immune response to the infection. In the present study, we have characterized the nasopharyngeal bacterial mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…While an important part of the research in this field, especially at the initial moments of the COVID-19 pandemic, has focused mainly on comparing the nasopharyngeal microbiota of SARS-CoV-2 positive individuals to uninfected controls independently on the symptomatology of those patients or the severity of their disease [ 44-49 , 51 , 52 , 57-63 ], many of the most recent studies have gone further and have examined the possible association between the nasopharyngeal microbiota and the COVID-19 disease severity or outcome (Table S1) [ 50 , 53-56 , 64-70 ]. The publications which only compared the nasopharyngeal microbiota composition of asymptomatic or paucisymptomatic SARS-CoV-2 positive subjects to negative healthy controls generally found little or no differences (Table S1) [ 44 , 63 , 65 ]. Thinking of the other extreme in respect to the severity of the COVID-19 disease, a couple of studies included only critically ill COVID-19 patients: on the one hand, Llorens-Rico and colleagues exclusively enrolled patients who were admitted to the intensive care unit for a variable period (Table S1) [ 60 ].…”
Section: Changes In the Nasopharyngeal Microbiota Of Sars-cov-2-infec...mentioning
confidence: 99%
“…While an important part of the research in this field, especially at the initial moments of the COVID-19 pandemic, has focused mainly on comparing the nasopharyngeal microbiota of SARS-CoV-2 positive individuals to uninfected controls independently on the symptomatology of those patients or the severity of their disease [ 44-49 , 51 , 52 , 57-63 ], many of the most recent studies have gone further and have examined the possible association between the nasopharyngeal microbiota and the COVID-19 disease severity or outcome (Table S1) [ 50 , 53-56 , 64-70 ]. The publications which only compared the nasopharyngeal microbiota composition of asymptomatic or paucisymptomatic SARS-CoV-2 positive subjects to negative healthy controls generally found little or no differences (Table S1) [ 44 , 63 , 65 ]. Thinking of the other extreme in respect to the severity of the COVID-19 disease, a couple of studies included only critically ill COVID-19 patients: on the one hand, Llorens-Rico and colleagues exclusively enrolled patients who were admitted to the intensive care unit for a variable period (Table S1) [ 60 ].…”
Section: Changes In the Nasopharyngeal Microbiota Of Sars-cov-2-infec...mentioning
confidence: 99%
“…The respiratory microbiome is crucial for human health [11]. Indeed, it modulates the immune response and contributes to counterattack respiratory infections [22,23] and its alteration has been involved in many inflammatory and respiratory diseases [24][25][26][27]. In the present study, we characterized the nasal microbiome of 55 pregnant women and 26 non-pregnant women and observed that pregnant women reported an increased alpha diversity.…”
Section: Discussionmentioning
confidence: 77%
“…The respiratory microbiome is crucial for human health [11]. Indeed, it modulates the immune response and contributes to counterattack respiratory infections [22,23] and its alteration has been involved in many inflammatory and respiratory diseases [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…At the genus level, we detected colonizers of different ecological habitats, as also observed in other BE studies [ 37 ]. The most abundant group, in both surface and air samples, was Burkholderia–Caballeronia–Parabulkholderia (11% and 47%, respectively), a vast group of Proteobacteria that was mostly environmental was also detected in the human nasopharyngeal tract [ 38 ], and including beneficial species as well as animal and plant pathogens and around twenty potential human pathogens (of the B. cepacia group) [ 39 ]. The microbiome profiles in surface and air were composed differently regarding other prevalent genera.…”
Section: Discussionmentioning
confidence: 99%